Extended Science: a powerful tool in widening participation - David John Harwood (Association for Learning Development in Higher Education (ALDinHE), 2016)
Year zero courses, as part of extended degree programmes, offer a robust and efficacious means of increasing participation in science and other areas of the university curriculum where graduate shortages have been identified, STEM subjects for example. This 23-year longitudinal study investigates the efficacy of this approach at one university and identifies the features which contribute to its success and may be transferable to other institutions and models. Quantitative and qualitative data are analysed and discussed. A particular feature of this approach is success in attracting, retaining and graduating mature returners as well as those with no prior familial history of participation in higher education. The critical importance of establishing a higher education learning culture also emerges.